Kinetic analysis of pulmonary neutrophil retention in vivo using the multiple-indicator-dilution technique - Schwab, Andreas J; Salamand, Agnes; Merhi, Yahye; Simard, Andre; Dupuis, Jocelyn (Journal of applied physiology (1985), 2003)
Multiple-indicator-dilution experiments were performed in the lungs of 13 anesthetized dogs by simultaneous bolus injection of 111In-labeled neutrophils, 51Cr-labeled red blood cells, and Evans blue-labeled albumin. Concomitant counts of unlabeled neutrophils were similar in pulmonary artery and aortic blood samples, demonstrating a dynamic balance across the lungs in the physiological state. Outflow profiles of labeled neutrophils were analyzed on the basis of a recirculatory pharmacokinetic model of labeled albumin. The outflow profiles of the recovered neutrophils were composed of a throughput component of circulating neutrophils and a component of reversibly marginated neutrophils. They were interpreted by a model incorporating neutrophil margination (transfer coefficient = 0.195 +/- 0.081 s-1), rapid demargination (0.054 +/- 0.027 s-1), and transfer to a slow marginated pool (0.023 +/- 0.018 s-1). It will be interesting to apply the analysis in future studies aimed at determining whether it could be a useful research tool to investigate the interactions between the pulmonary endothelium and neutrophils in physiological and diseased states.